Book “Masters of Deceit” by J. Edgar Hoover as an Ideological Basis of the Concept of “Red Scare” and Anti-Communism in the USA - Y. A. Levin (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to the formation of the image of such a phenomenon as the “Red Threat” in the literary work of FBI Director John Edgar Hoover. It is affirmed that a special position in the US executive power system, along with a certain popularity in the 30-50s of the 20th century, made Edgar Hoover and his ideas significant both for the internal political life of the United States and, to some extent, for the foreign policy of this country. It is emphasized that the publication “Masters of Deceit: the history of communism in America and how to deal with it” has become for its time an important ideological and political-philosophical basis in the formation of a powerful anti-communist movement in the United States against the backdrop of the Cold War. It is noted that this book is of interest from the point of view of analyzing how America’s major anti-communists understood the term communism , the history and essence of classical Marxism, Marxism-Leninism, the revolution in Russia and the changes that occurred in Soviet Russia after it, Stalinism and its consequences. It is indicated that the author of the book not only analyzes the most important moments in the history of world and Russian communism, but also tries to understand how the communist ideology has developed in the USA, who the American communists are, what their goals are, etc.